2021
DOI: 10.1002/aenm.202101698
|View full text |Cite
|
Sign up to set email alerts
|

Layered Transition Metal Oxides as Ca Intercalation Cathodes: A Systematic First‐Principles Evaluation

Abstract: to Mg, and they are much higher than Li (Ca: 4.2%, Mg: 2.3%, Li: 0.002% of Earth's crust), suggesting low materials cost and a secure supply chain. Despite the inherent advantages of Ca-based chemistry, much less research efforts have been put in Cathan in Mg-based chemistries.The emergence of Ca batteries has been hampered by the paucity of known materials functioning as electrolytes and electrodes. Recent development of electrolytes enabling facile Ca plating/ stripping [3] and fast Ca intercalation into gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…The conversion reaction is predicted by the density functional theory calculation to occur for a two-electron transfer per Ni ion with the intercalation of Ca ions in NiO 2 , while the intercalation reaction is predicted for a one-electron transfer. 42,43 It is possible that the reaction with CaI 2 initially proceeds as the intercalation of Ca ions, but the high diffusion barrier of Ca ions in Br-NMC impedes the diffusion of Ca ions into the particle interior, leading to the accumulation of Ca ions at the surface. The octahedral site in Br-NMC is not amenable for facile Ca-ion diffusion, which can be realized in the prismatic site.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conversion reaction is predicted by the density functional theory calculation to occur for a two-electron transfer per Ni ion with the intercalation of Ca ions in NiO 2 , while the intercalation reaction is predicted for a one-electron transfer. 42,43 It is possible that the reaction with CaI 2 initially proceeds as the intercalation of Ca ions, but the high diffusion barrier of Ca ions in Br-NMC impedes the diffusion of Ca ions into the particle interior, leading to the accumulation of Ca ions at the surface. The octahedral site in Br-NMC is not amenable for facile Ca-ion diffusion, which can be realized in the prismatic site.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…The octahedral site in Br-NMC is not amenable for facile Ca-ion diffusion, which can be realized in the prismatic site. 43 Although there has been no report for Caion diffusion in the ternary NMC-type layered compound, computational studies of the closely related layered NiO 2 have reported a high Ca-ion diffusion barrier (>650 meV) for both charged and discharged NiO 2. 44 Once the surface concentration of Ca ions becomes sufficiently high, the conversion reaction occurs, resulting in the formation of a thin coating layer of CaO, which assumes the same cubic structure as NiO, and the displacement of Li ions into the particle interior.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculation is an approach to the quantum mechanical many-body problem, in which the ground-state energy of an M-electron system can be treated as a function only of the electron density. There is considerable interest in utilizing DFT calculations to investigate electrode properties for battery applications. ,, Numerous key properties of electrode materials, such as equilibrium voltages and their corresponding profiles, ionic mobility, and thermal and electrochemical stabilities can be identified using these computational techniques. The reliability of the computational results can be further used to design and develop new materials for experiments rather than the conventional trial-and-true approaches. In addition, surface and defect chemistries existing in the materials can also be projected toward achieving high-performance battery application.…”
Section: Computational and Experimental Analyses For Cathodes Of Cibs...mentioning
confidence: 99%
“…As a result, Ca 3 Co 2 O 6 , CaCo 2 O 4 , and [Ca 2 CoO 3 ]­[CoO 2 ] 1.62 were successfully prepared using the Pechini method. Systematic computational studies were also performed by Zapol et al for finding suitable Ca cathode materials . They evaluated CaTM 2 O 4 materials (TM: Ti, V, Cr, Mn, Fe, Co, and Ni) in terms of their thermodynamic stability, average intercalation voltage, energy density, preference for intercalation versus conversion, synthesizability, cation mobility, and electronic structure.…”
Section: Computational and Experimental Analyses For Cathodes Of Cibs...mentioning
confidence: 99%